Phosphoric acid functionalized pre-sintered meso-silica for high temperature proton exchange membrane fuel cells - Zeng, J.; He, B.; Lamb, K.; De Marco, Roland; Shen, P.; Jiang, San Ping (The Royal Society of Chemistry, 2013)
An inorganic proton exchange membrane based on sintered mesoporous silica and phosphoric acid was developed with a high proton conductivity of 0.06 S cm−1 at 200 °C, achieving an excellent power output of 689 mW cm−2 in H2 at 190 °C and 200 mW cm−2 in methanol at 200 °C with no external humidification.